AMILORIDE ATTENUATES ALDOSTERONE-INDUCED RENAL INJURIES VIA THE SUPPRESSION OF PLASMIN ACTIVITY IN THE KIDNEY. (April 2021) - Kakizoe, Yutaka; Iwata, Yasunobu; Nakagawa, Terumasa; Deng, Qinyuan; Adachi, Masataka; Izumi, Yuichiro; Kuwabara, Takashige; Mukoyama, Masashi
Abstract : Objective: Aldosterone has been known to exert direct detrimental effects on the kidney independently of its hemodynamic effects. We have reported that a serine protease plasmin was highly activated in the kidney of aldosterone/salt-treated rats and that plasmin caused kidney injuries through the induction of inflammatory and profibrotic cytokines. Amiloride is one of the potassium-sparing diuretics and it inhibits epithelial sodium channel (ENaC). On the other hand, it was reported that lower dose amiloride attenuated renal injuries without blood pressure (BP) lowering effect in salt-sensitive hypertension model rats. Because amiloride has a pleiotropic effect to inhibit urokinase-type plasminogen activator (uPA), we evaluated whether amiloride could attenuate aldosterone-induced renal injuries via the suppression of uPA-plasmin cascade in the kidney. Design and method: Nine-week old male uninephrectomized Sprague-Dawley rats were divided into following groups (1) normal salt diet (0.3%NaCl; NS), (2) aldosterone + high salt diet (0.75 μg/kg/h, subcutaneously + 8.0% NaCl; Ald+HS), and (3) aldosterone + high salt diet + amiloride (1 mg/kg/day, subcutaneously; Ami). Systolic BP (SBP) measurement and 24 h urine collection were performed every second week, and rats were sacrificed at 4 week. Renal plasmin activities were evaluated by zymography. Results: Amiloride did not affect either electrolytes in serum and urine nor blood pressure, indicating that the current dose of amiloride did not inhibit ENaC in the distal nephron [SBP (mmHg): NS, 115 ± 11; Ald+HS, 169 ± 17; Ami, 161 ± 21.]. Amiloride suppressed renal plasmin activation, and mitigated urinary protein excretion, renal dysfunction and histological damages as well as mRNA expression of kidney injury markers induced by aldosterone/salt [urinary protein (mg/day): NS, 10 ± 3; Ald + HS, 381 ± 61; Ami, 161 ± 22.]. Conclusions: Our findings indicate that pleiotropic effects of amiloride to inhibit uPA-plasmin cascade may be beneficial for the treatment of aldosterone-associated renal injuries.